Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.11646/phytotaxa.238.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Andean genus Deprea (Physalideae, Solanaceae): testing the generic circumscription

Abstract: Deprea (Solanaceae) is a small South American genus of 10 species occurring in Andean areas from Venezuela to Bolivia. The circumscription of Deprea has been repeatedly modified in recent years, with new species being described and others transferred into or out of the genus. The relationships of Deprea to other genera of Solanaceae are still poorly understood, although it seems to be closely related to Larnax. A phylogenetic analysis was performed to test the monophyly of Deprea. Sequences from three molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The phylogenetic evidence is further supported by results from recent extensive field collecting and taxonomic work which have shown that characters utilized to distinguish the two genera are not useful, and increasing number of species are found to have intermediate features between the two genera (see Table 1, Deanna et al 2014b; Carrizo et al submitted). Consequently, this paper synonymises Larnax under Deprea , expands the morphological circumscription of Deprea , and transfers the remaining Larnax species to Deprea , presenting all 32 new combinations, and a list of all currently accepted 45 names in Deprea .…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…The phylogenetic evidence is further supported by results from recent extensive field collecting and taxonomic work which have shown that characters utilized to distinguish the two genera are not useful, and increasing number of species are found to have intermediate features between the two genera (see Table 1, Deanna et al 2014b; Carrizo et al submitted). Consequently, this paper synonymises Larnax under Deprea , expands the morphological circumscription of Deprea , and transfers the remaining Larnax species to Deprea , presenting all 32 new combinations, and a list of all currently accepted 45 names in Deprea .…”
Section: Introductionmentioning
confidence: 67%
“…Deprea and Larnax are interesting for their chemical and medicinal value (Cardona et al 2005, Misico et al 2011, Casero et al 2015), but also for their controversial circumscription and position within the Physalideae tribe (Olmstead et al 2008, Särkinen et al 2013, Carrizo García et al submitted). Various authors have transferred species between the two genera for many years (Miers 1849, D´Arcy 1973, 1993, Sawyer 2001, Leiva González et al 2005) and redefined their limits (Hunziker 2001, Sawyer 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other changes include the merging of Larnax Miers into Deprea Raf. (Carrizo García et al, ; Deanna et al, ) and the renaming of Leucophysalis viscosa (Schrad.) Hunz.…”
Section: Methodsmentioning
confidence: 99%